1989
DOI: 10.1161/01.cir.80.6.1846
|View full text |Cite
|
Sign up to set email alerts
|

Progressive impairment of regional myocardial perfusion after initial restoration of postischemic blood flow.

Abstract: The "no-reflow" phenomenon, the occurrence of areas with very low flow in hearts reperfused after ischemia, is thought to be largely established at the time of reperfusion as a result of microvascular damage induced by ischemia. In the present study we sought to determine whether additional impairment of tissue perfusion might also occur during the course of reperfusion. Open-chest dogs were subjected to 90 minutes of left circumflex coronary artery occlusion and reperfused for 2 minutes (n=7) or 3.5 hours (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
208
2
12

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(231 citation statements)
references
References 61 publications
9
208
2
12
Order By: Relevance
“…Previous studies have demonstrated in the heart and the isolated cells of which the heart is comprised that radical generation is greatly enhanced in both cardiac myocytes and endothelium (16,(18)(19)(20)(21)(22). In the postischemic heart, alterations in endothelial vasodilatory function occur because of a loss of NO production from eNOS, which in turn limits CF and triggers a range of problems including platelet and leukocyte adhesion and aggregation, leading to capillary plugging and vascular reocclusion (24,25). Thus, impaired endothelial function is of critical importance in patients with acute coronary syndromes, and restoration of normal endothelial vasodilator function would tend to prevent problems of microvascular occlusion after acute recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated in the heart and the isolated cells of which the heart is comprised that radical generation is greatly enhanced in both cardiac myocytes and endothelium (16,(18)(19)(20)(21)(22). In the postischemic heart, alterations in endothelial vasodilatory function occur because of a loss of NO production from eNOS, which in turn limits CF and triggers a range of problems including platelet and leukocyte adhesion and aggregation, leading to capillary plugging and vascular reocclusion (24,25). Thus, impaired endothelial function is of critical importance in patients with acute coronary syndromes, and restoration of normal endothelial vasodilator function would tend to prevent problems of microvascular occlusion after acute recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…The use of extra-corporeal circulation has been shown to start systemic inflammation, and also to induce ischemia reperfusion-related release of ROS [20][21][22]. The authors demonstrated that, preoperatively, 83% of the patients had a selenium deficiency, and that all patients had a decreased s-selenium level when reaching the intensive care unit after their operation.…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…Even with gold standard technology (TTC staining) in the experiment, infarcted tissue is only recognized as such after several hours of reperfusion, and no distinction between myocardium infarcting during ischemia and during reperfusion is possible. No-reflow, as evidenced by lack of endothelial staining by thioflavin in the experiment [13], develops rapidly during early reperfusion and progresses over time [1,22,23]. Most studies indicate that no-reflow areas are This comment refers to the article available at…”
mentioning
confidence: 99%
“…No-reflow, as evidenced by lack of endothelial staining by thioflavin in the experiment [13], develops rapidly during early reperfusion and progresses over time [1,22,23]. Most studies indicate that no-reflow areas are confined to areas of infarcted myocardium [1,13]. However, this notion of a confinement of no-reflow to infarcted myocardium is based on experimental studies with mechanical occlusion and reperfusion of virgin coronary arteries or clinical studies using MRI several days after established reperfusion.…”
mentioning
confidence: 99%